In Vivo Evaluation of an Antibody-Functionalized Lipoidal Nanosystem for Schistosomiasis Intervention - Tayo A. Adekiya; Pradeep Kumar; Pierre P. D. Kondiah; Yahya E. Choonara (MDPI AG, 2022)
This study employed nanotechnological techniques to design and develop a praziquantel nanoliposomal (NLP) system and surface-functionalized the NLP with anti-calpain antibody (anti-calpain-NLP) for targeted praziquantel (PZQ) delivery in the treatment of schistosomiasis. Anti-calpain-NLPs were prepared and validated for their physicochemical parameters, in vitro and in vivo toxicity, drug entrapment efficiency (DEE), drug loading capacity (DLC), drug release, and parasitological cure rate. The particle sizes for the formulated nanoliposomes ranged from 88.3 to 92.7 nm (PDI = 0.17-0.35), and zeta potential ranged from −20.2 to −31.9 mV. The DLC and DEE ranged from 9.03 to 14.16 and 92.07 to 94.63, respectively. The functionalization of the nanoliposome surface was stable, uniform, and spherical. Fourier-transform infrared (FTIR), thermal behavior and X-ray powder diffraction (XRPD) analysis confirmed that the anti-calpain antibody and PZQ were attached to the surface and the nanoliposomes inner core, respectively. The drug sustained release was shown to be 93.2 and 91.1% within 24 h for NLP and anti-calpain-NLP, respectively. In the in vitro analysis study, the nanoliposome concentrations range of 30 to 120 μg/mL employed revealed acceptable levels of cell viability, with no significant cytotoxic effects on RAW 264.7 murine macrophage as well as 3T3 human fibroblast cells. Biochemical markers and histopathological analysis showed that the formulated nanoliposomes present no or minimal oxidative stress and confer hepatoprotective effects on the animals. The cure rate of the anti-calpain-NLP and PZQ was assessed by parasitological analysis, and it was discovered that treatment with 250 mg/kg anti-calpain-NLP demonstrated greater activity on the total worm burden, and ova count for both the juvenile and adult schistosomes in the intestine and liver of infected mice. The findings so obtained supported the ability of oral anti-calpain-NLP to target young and adult schistosomes in the liver and porto-mesenteric locations, resulting in improved effectiveness of PZQ.